Investigation of physical, chemical and rheological properties of bituminous binders modified with different rejuvenators - Yalcin, Erkut (Gazi Univ, Fac Engineering Architecture, 2022)
Purpose: We have used these two rejuvenator to carry out a broad-based study of their effects on the mechanical, rheological, and chemical structures of bitumen binders. The reclaimed asphalt mixtures were composed of mixtures of RAP materials, pure bitumen, aggregates, and the selected rejuvenator. Despite the fact that the rejuvenators were used as a means of measuring their amelioration performance on the characteristics of the aged binders found in RAP, it was also seen that these rejuvenators also affected the performance of mixtures made with pure bitumen binders. Theory and Methods: This study focuses on the effects on the unaged binder of two rejuvenators by evaluating their effects at five different ratios. Penetration, softening point, elastic recovery, flash point, force ductility, brookfield viscosity, and dynamic shear rheometer (DSR) tests were conducted to gain an understanding of the physical and mechanical characteristics of bitumen binders after being mixed with these rejuvenators. Results: The addition of rejuvenators to pure bitumen reduced the penetration and softening point values, while increasing the flash point values. R2 rejuvenator tended to soften the pure bitumen more than that R1. R1 and R2 addition significantly reduced the binder viscosity. R2 reduced the viscosity of the pure bitumen more than R1. the increase in additive content led to a decrease in complex modulus with both types of additives. The reduction in the complex modulus was observed mostly with R1 addition. R2 modification led to the highest complex modulus values. In R1 modification, it was observed that the increase in phase angles with increased additive content was greater when compared to the R2 modification. Conclusion: Both additives used in the study led to promising results for their utilizations as rejuvenator in recycled asphalt mixtures. Tests conducted to measure consistency and rheological tests demonstrated that both of these additives may provide rejuvenating benefits to the bitumen being used. Tests also led us to conclude that both of these rejuvenators can provide benefits to the utilization of RAP materials from both environmental and economic perspectives, but the results also indicated that the R2 rejuvenator provides better performance than does the R1.
Farklı gençleştiricilerle modifiye edilmiş bitümlü bağlayıcıların fiziksel, kimyasal ve reolojik özelliklerinin araştırılması
Keywords: Bitumen; Rejuvenator; Rheology; Chemical Compounds; Modification